A novel genetic model to explore the Brenner hypothesis: Linking nephron endowment and number with hypertension. (September 2017) - Didion, Sean P.
Abstract: Nephron endowment, the total number of nephrons an individual is born with, is determined by both genetic and environmental factors during embryonic development. In 1988, Brenner hypothesized that there was an inverse relationship between nephron number and hypertension. Over the course of one's lifetime it is predicted that even healthy individuals will lose a significant percentage of nephrons as part of normal aging. Thus, a low nephron endowment at birth or in combination with age- or disease-related nephron loss could pre-dispose individuals to the development of hypertension. Currently, it is not clear what minimal number (ie, threshold) of nephrons is associated with susceptibility to glomeruli injury or hypertension, due in part to the lack of relevant animal models. The BPH2 mouse is a unique genetic model of hypertension that has a normotensive line (BPN3 mice) as well as a hypotensive line (BPL1 mice) derived from the original breeding of eight common inbred strains of mice. Thus, we hypothesize that the differences in blood pressure observed in BPH2, BPN3, and BPL1 mice will correlate inversely with nephron number as predicted by the Brenner hypothesis. If our hypothesis is true, then the BPH2 mouse model will provide a unique experimental model to study the impact of nephron endowment and nephron number on susceptibility to renal injury and hypertension.